Modern Applications of Aluminium Foams - Garai, Flórián (International Journal of Engineering and Management Sciences, 2020)
The implementation of aluminium alloy foam has more and more attention. Application of closed cell aluminium foam has made an impact in automobile and aerospace applications where crash energy absorption, vibration and weight reduction are obligatory [1,2,3]. The aluminium alloy foam is an advanced lightweight material providing high strength and stiffness at relatively low density. The technological use of aluminium alloy foam is difficult with the currently available technologies. In the case of open cell aluminium foams, the most common research areas for application are heat exchanger components, filters and sound damping elements [3]. The manuscript focuses on the manufacturing techniques of the aluminium alloy foams according to the application areas. First step is the investigation of the requirements for the application: what are the loads and the circumstances and why can we use aluminium foams. Second step is the knowledge of the producing methods of the foam or the component. And the last step is the investigation of the possible testing methods.